WHAT IF PAULO FREIRE TAUGHT ENGLISH FOR SPECIFIC PURPOSES IN A FEDERAL INSTITUTE IN BRAZIL? - Almeida, Daniele Barbosa de Souza; Amorim, Simone Silevira; Kress, Tricia Marie (ARACÊ, 2025)
According to Confucius, an image is worth more than a thousand words. However, we believe a critical perspective is necessary to access the communicative potential of an image. This article aims to defend that learning English can contribute to critical thinking and the exercise of citizenship if viewed from a Freirean perspective. To reach this objective we analyzed an image from the Critical Pedagogy and Education Research Methods in the US and Brazil Project database using the Image Perception Systematization Framework by Amorim and Kress (2020) to reflect on the possibilities of language teaching for Specific Purposes in Brazil from a Freirean perspective. This qualitative research is grounded in the theories of Freire and Giroux. We believe that some changes need to be made for language teaching in Brazil to assume the political task of contributing to the exercise of critical thinking.